ΑKlotho protein has therapeutic activity in contrast-induced acute kidney injury by limiting NLRP3 inflammasome-mediated pyroptosis and promoting autophagy. (May 2021) - Zhu, Xuying; Li, Shu; Lin, Qisheng; Shao, Xinghua; Wu, Jingkui; Zhang, Weiming; Cai, Hong; Zhou, Wenyan; Jiang, Na; Zhang, Zhen; Shen, Jianxiao; Wang, Qin; et al.
Abstract: Contrast-induced acute kidney injury (CI-AKI) is a main cause of hospital-acquired renal failure. Nevertheless, limited measures have been shown to be effective for the treatment of CI-AKI. Here, we demonstrated that αKlotho, which is highly expressed in kidney, has therapeutic activity in CI-AKI. Our data showed that αKlotho expression levels were decreased both in the kidney and serum of CI-AKI mice. Administration of αKlotho protein protected the kidney and HK-2 cells against contrast-induced injury. Mechanistically, αKlotho reduced contrast-induced renal tubular cells pyroptosis by limiting NLRP3 inflammasome activation. Meanwhile, αKlotho up-regulated autophagy via inhibiting the AKT/mTOR pathway and decreased mitochondrial ROS level. Inhibition of autophagy blunted the suppression effect of αKlotho on NLRP3 inflammasome activation and cell pyroptosis in contrast-treated HK-2 cells. Taken together, our data suggest that αKlotho protein protects against CI-AKI through inhibiting NLRP3 inflammasome-mediated pyroptosis, which is likely by promoting autophagy. αKlotho may be a promising therapeutic strategy for CI-AKI. Graphical Abstract: ga1